The Use of Subtitle in Cartoon Movie Entitled “Frozen 2” as A Media in Improving Students’ Vocabulary Mastery on SMP Purnama 2 Semarang in Academic Year 2023 - Tanzila Alfi Hasanah; Dyah Nugrahani; Ajeng Setyorini (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The research aimed to investigate the effectiveness of using English subtitles from the movie